2008
DOI: 10.1111/j.1537-2995.2008.01814.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐A and anti‐B titers in pooled group O platelets are comparable to apheresis platelets

Abstract: Anti-A and anti-B titers in group O PPLTs are comparable to those reported in group O SDPs and significantly lower than titers reported in AHTR. A critical direct agglutinin titer of 64 for identifying high-titer units by gel is too low and should be increased to 128 or higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 29 publications
(37 reference statements)
4
69
0
Order By: Relevance
“…Had ‘high titer' been defined in this study as ≥256, 26% of group O apheresis PLTs would have been labeled as such which is similar to the 39% of ‘high titer' group O apheresis PLTs described above [3]. Using an IgG titer of ≥64, approximately half of the group O apheresis PLTs in this study [5] would have been labeled ‘high titer', a figure that is similar to a previous report of the prevalence of ‘high titer' pooled group O PLT units [4]. In contrast, Quillen et al [6] found that half of their group O apheresis PLTs would have been considered ‘high titer' at a screening dilution of 1:150, while 25% of these donations are handled as ‘high titer' PLTs with their current threshold of 1:250.…”
Section: Part 1: Plt Transfusion and Abo Compatibilitysupporting
confidence: 68%
See 2 more Smart Citations
“…Had ‘high titer' been defined in this study as ≥256, 26% of group O apheresis PLTs would have been labeled as such which is similar to the 39% of ‘high titer' group O apheresis PLTs described above [3]. Using an IgG titer of ≥64, approximately half of the group O apheresis PLTs in this study [5] would have been labeled ‘high titer', a figure that is similar to a previous report of the prevalence of ‘high titer' pooled group O PLT units [4]. In contrast, Quillen et al [6] found that half of their group O apheresis PLTs would have been considered ‘high titer' at a screening dilution of 1:150, while 25% of these donations are handled as ‘high titer' PLTs with their current threshold of 1:250.…”
Section: Part 1: Plt Transfusion and Abo Compatibilitysupporting
confidence: 68%
“…Another study revealed that 60% of group O pooled PLT units, which consisted of 4-5 individual units, harbored an anti-A and/or anti-B titer of ≥64 by the gel technique [4]. Using this technique, the mean anti-A titer was 64 and the mean anti-B titer was 32.…”
Section: Part 1: Plt Transfusion and Abo Compatibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a small number of institutions prospectively screen group O single donor apheresis PTLs for the presence of high titer agglutinins. (5) Similarly, there is a shortage of identical organ and blood donors. Both situations need blood bank strategies to minimize the biological effects of ABO antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Screening donors for a predefined high titered anti-A/ anti-B likely reduces the incidence, but to date, there is no consensus on immunoglobulin class or what level constitutes a critical titer. 6,[35][36][37] Volume reduction or replacing the plasma with saline may mitigate such minor ABO-mismatched hemolysis but compromise platelet integrity and function. 38 Our work suggests that it is prudent to investigate a clinically significant drop in hemoglobin for minor ABO-mismatched recipients of minor ABO-mismatched products who may have a hematologic myelopathy.…”
Section: Discussionmentioning
confidence: 99%